Quantitative risk assessment of rabies being introduced into mainland France through worldwide noncommercial dog and cat movements. Issue 5 (21st June 2022) - Crozet, Guillaume; Rivière, Julie; Rapenne, Elisa; Cliquet, Florence; Robardet, Emmanuelle; Dufour, Barbara
Abstract: France has been rabies‐free among nonflying mammals since 2001. Despite this status, the rabies virus has been introduced several times through noncommercial pet movements, posing a threat of infection by this 100%‐lethal zoonosis among local animal and human populations. To quantify the risk of rabies being introduced through worldwide noncommercial dog and cat movements, we performed a quantitative risk assessment using stochastic scenario tree modeling. The mean annual probability of at least one rabies introduction incident was 0.35 (median: 0.24, 90% prediction interval (PI) [0.04; 0.98]) and the mean annual number of rabies‐infected pets introduced through pet movements was 0.96 (median: 0.27, 90% PI [0.04; 3.88]). These results highlight a nonnegligible, even high risk due to the associated consequences of such events. In alternative scenario testing, preventive anti‐rabies vaccination proved to be an effective measure since removing the vaccination requirement led to a > 15‐fold increase in risk. The serological testing requirement had less of an effect (approximately two‐fold increase when removed) and the posttest waiting period to ensure that antibodies were not linked to an infection had a negligible effect. Any change in pet owner compliance, especially regarding vaccination, could have a major impact on the risk. This study also shows that reinforced border control staff training could be more effective in reducing risk than more frequent checks. These results provide quantitative data for assessing the probability of the rabies virus entering France, and could help policymakers decrease this risk in rabies‐free areas.